2019
DOI: 10.1371/journal.pone.0221817
|View full text |Cite
|
Sign up to set email alerts
|

Loss of control as a violation of expectations: Testing the predictions of a common inconsistency compensation approach in an inclusionary cyberball game

Abstract: Personal control relies on the expectation that events are contingent upon one’s own behavior. A common ‘inconsistency compensation approach’ posits that a violation of expectancies in social interaction triggers aversive arousal and compensatory effort. Following this approach, we tested the hypothesis that interventions affecting participants' decisions violate the expected personal control. In a modified version of the established cyberball paradigm, participants were not excluded, but consistently included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(54 citation statements)
references
References 65 publications
3
51
0
Order By: Relevance
“…Recently, Niedeggen and colleagues [ 19 ] modified the Cyberball paradigm, in which personal control was threatened ( Intervention Cyberball ). To challenge the participants’ decisional autonomy, a putative supervisor was introduced, who can overrule the participant’s decision on the recipient of his/her ball throw and select a different ball recipient.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Niedeggen and colleagues [ 19 ] modified the Cyberball paradigm, in which personal control was threatened ( Intervention Cyberball ). To challenge the participants’ decisional autonomy, a putative supervisor was introduced, who can overrule the participant’s decision on the recipient of his/her ball throw and select a different ball recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the participant remains included, i.e., the probability of ball reception remains unchanged, but his/her personal control is challenged by the intervention of the supervisor. Correspondingly, self-reports provided in the NTQ indicated that participants did not feel a threat to belonging, but reported a significantly increased threat in the scale need for control [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the induction of FRN, several studies have also discovered that behaviors that cause a sense of violation of rules or expectations can induce the related subsequent P300 component (Niedeggen et al, 2019;Porcaro et al, 2019;Zhan et al, 2020). The P300 component that appears after the FRN amplitude peak usually reaches its maximum positive amplitude 200-600 ms after stimulation.…”
Section: P300 Componentmentioning
confidence: 99%